BIOMONITORING KADAR TIMBAL (Pb) PADA ANAK JALANAN DI KOTA SAMARINDA - Hansen Hansen; Muhammad Habibi; Ainur Rachman (Dian Nuswantoro Semarang, 2019)
Air is a very important factor in life, so air is a natural resource that must beprotected, as for its utilization, it must always be wise to pay attention to futuregenerations. Changes in the air environment are generally caused by airpollution, the entry of pollutants in the form of gases, small particles or aerosolsinto the air. The growth of motorized vehicles in Samarinda will have a largepotential to reduce the quality of the air environment. A decrease in the quality ofthe air environment can be caused by the emission of motor vehicles containingheavy metals including Lead (Pb). The problem formulation in this study is howmuch exposure to Lead (Pb) on street children in Samarinda City. The purpose ofthis study is to measure lead levels (Pb) in the blood of street children inSamarinda City. his study uses observational analytic research methods,conducts interviews and uses questionnaires and conducts examination andanalysis of Lead (Pb) in the Laboratory. The design of this study uses crosssectional. Based on the results of the study of Biomonitoring Lead Level (Pb) inblood on street children in Samarinda City the average Lead Level (Pb) in bloodin street children in Samarinda City was 0.28615 mg/l (28.615 Î¼g/dl) with astandard deviation value of 0, 299848 which means Lead Level (Pb) above thethreshold set by the Center for Disease and Prevention 10-19 Î¼g/dl.Keyword: Biomonitoring, Lead, Street Children